Althusser's Mirror - Carsten Strathausen (Studies in 20th & 21st Century Literature, 1994)
Jacques Lacan significantly influenced Althusser's accounts of ideology and the subject. Althusser's belief that science is a discourse without a subject parallels Lacan's belief that in the Symbolic Order the Subject and the Other are alienated. Althusser's account of interpellation, which explains how ideology recognizes individuals as subjects, takes for granted Lacan's notion of the mirror stage. Althusser repudiates the plenitude of the subject, whose interpellation conceals its lack; Lacan shows that the subject's failure to express itself in language makes the subject a void. However, Althusser, whose subject is too much like Lacan's ego, fails to distinguish between the "I" of the split subject and the "ego" of the subject's imaginary self-identity. What is more, Althusser rejects the self-consciousness implied by the subject's lack of plenitude and its suturing interpellation.
Keywords: Jacques Lacan; Althusser; ideology; subject; science is a discourse; science; Symbolic Order; Subject; Other; alienated; interpellation; individuals; mirror stage; plenitude of the subject; failure; subject' s failure; ego; imaginary self-identity; self-consciousness